Sensitive label-free electron chemical capacitive transducer signal for D-dimer electroanalyses - Marquesa, Simone M. (2015)
Supplementary data associated with this article can be found, in the online version, at: http://dx.doi.org/10.1016/j.electacta.2015.09.169.